Knowledge, Attitude, and Practices of Infection Prevention and Control among Healthcare Workers - Catacutan, Estela Q.; Joseph, Novem Catherine E.; Marcial, Dave E. (Silliman Journal, 2025)
The study evaluates infection prevention and control (IPC) practices among Bais and Bindoy District Hospital healthcare workers. It aims to gauge their knowledge, attitudes, and practices concerning IPC, analyzing the relationships between these factors and respondents' demographic profiles. Using a non-experimental descriptive-correlational design, the researchers encompassed all healthcare professionals at these hospitals and employed a validated survey questionnaire. Statistical tools such as Cronbach Alpha, percentage, Mann Whitney U Test, Chi-square, and Kruskal-Wallis were utilized. Findings reveal adequate knowledge among respondents (mean score: 1.50), indicating lower susceptibility to hospital-acquired infections. The study also highlights a significant relationship between demographic profiles and knowledge and practices in IPC, though not with attitudes. No significant differences were found in IPC attitudes, knowledge, or practices when segmented by sex, age, length of service, or working department. The study underlines the lack of training courses as a key factor influencing professionals' knowledge and practices in IPC, recommending regular and comprehensive training programs alongside stringent adherence to updated standard operational procedures for all healthcare workers (HCWs) at these hospitals.